THE IDEOLOGY HIDDEN BEHIND THE FEMALE SONG LYRICS IS BEHIND THE VEIL OF KEKASIH GELAPKU SONG LYRICS - Ajid Mustopa; Suparna Suparna; Dede Abdurrohman (IKIP Siliwangi, 2020)
This research shows about the ideology hidden behind the song lyrics. The research method used is critical discourse analysis with analytical techniques using a substantive theoretical framework, namely hegemony, ideology, and feminism as well as the theory of study analysis from Michael Foucault. The results showed that the song was a study to marginalize one woman, but strengthen other women. The ability to reflect the listener's ideology towards patriarchal ideology, and use it as a force of encouragement that being the second is not bad.